A variação e o preconceito linguístico na escola à luz sociolinguística e dos PCNs - Michelon, Talita Mayara; Martins, Maria Angélica Seabra Rodrigues [UNESP] (My University, 2012)
Nowadays questions involving the use of social and cult language approach at the school has produced discussions between teachers, thus the use of the linguistics registers different of that considered correct aren’t accept or analyzed in the context of the classroom, although the national curriculum framework recommend it. So, there are many difficulties of socialization by the students principally that ones who come from the surrounding regions, if they use the linguistics approach differently of the accepted as a model. The objective of this paper is to analyze those questions, involving variation and prejudice in the classroom context, from the Sociolinguistics point of view how this science has been applied in the classroom context, considering the curriculum proposals of 1992 and the national curriculum .

Na atualidade, questões envolvendo a linguagem oral e o emprego da norma culta na escola tem gerado discussões entre os professores, uma vez que o emprego de registros diferenciados dos considerados corretos não é devidamente aceito e/ou analisado em sala de aula, ainda que os Parâmetros Curriculares Nacionais o recomende. Dessa forma, muitas são as dificuldades de socialização encontradas por alunos, principalmente em escolas de periferia, caso utilizem registros linguísticos diferenciados do aceito como padrão. O objetivo deste trabalho é o de analisar as questões envolvendo variação e preconceito, à luz da Sociolinguística, observando como essa ciência tem sido aplicada no contexto de sala de aula, a partir da análise das Propostas Curriculares de 1992 e dos Parâmetros Curriculares Nacionais de 1998
Keywords: Sociolinguística; Variação linguística; Preconceito linguístico